Determinants of the perception of FinTech companies as environmentally friendly: European consumers' perspective - Dariusz Piotrowski; Anna Piotrowska (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The aim is to identify the determinants of the perception of FinTech companies as environmentally friendly institutions. Research Design & Methods: The empirical base used in the work comprises data obtained in a survey conducted using computer-assisted web interviews of 2 000 respondents from the United Kingdom, Germany, Poland, and Ukraine. We used the ordinary logit models in the data analysis. Findings: We identified the perceived benefits of using artificial intelligence (AI) technology in the financial sector and personal values and beliefs regarding sustainable development as the key factors determining whether FinTech companies are perceived as environmentally friendly institutions. Moreover, we found that education and financial knowledge are significant determinants. Implications & Recommendations: For FinTech companies to be perceived as environmentally friendly, decision-makers must take actions supporting environmental sustainability and implement an appropriate communication policy. Building a green institutional image is supported by educating consumers about finance, promoting ecological responsibility, and encouraging more frequent use of financial applications. It is also important to highlight environmental initiatives while avoiding greenwashing, as individuals engaged in environmental protection are particularly sensitive to manipulation in this area. The findings of the study can also serve to increase the effectiveness of communication between FinTech companies and market participants in the area of environmental protection. Considering the importance of the variable related to the AI use in finance, the messaging should emphasise the positive environmental impact of digital technologies employed by FinTech companies. Contribution & Value Added: The study significantly contributes to the development of green FinTech research, as it is the first to address how FinTech companies come to be regarded as environmentally friendly. Identifying the determinants of the relevant perceptions is particularly important since the literature shows that most consumers are not convinced of the beneficial impact of banks and FinTech companies on the environment. The study's particular contribution is the identification of universal determinants independent of the respondents' country of origin, which FinTech company managers should consider when designing services and communicating with consumers. Empirical evidence also indicates that the value-belief-norm theory contributes to explaining the perception of FinTech companies as green. We should associate the uniqueness of the work with the use of data obtained in a survey of respondents from several European countries with different levels of financial market development and different degrees of implementation of the UN Sustainable Development Goals.
Keywords: G23; O44; Q55; 330; artificial intelligence in finance; digital financial services; green FinTech; sustainable development goals (SDGs); value-belief-norm (VBN) theory